The EPIC-Norfolk Eye Study: rationale, methods and a cross-sectional analysis of visual impairment in a population-based cohort. Issue 3 (19th March 2013) - Khawaja, Anthony P; Chan, Michelle P Y; Hayat, Shabina; Broadway, David C; Luben, Robert; Garway-Heath, David F; Sherwin, Justin C; Yip, Jennifer L Y; Dalzell, Nichola; Wareham, Nicholas J; Khaw, Kay-Tee; Foster, Paul J
Abstract : Objectives: To summarise the methods of the European Prospective Investigation of Cancer (EPIC)-Norfolk Eye Study, and to present data on the prevalence of visual impairment and associations with visual impairment in the participants. Design: A population-based cross-sectional study nested within an on-going prospective cohort study (EPIC). Setting: East England population (the city of Norwich and its surrounding small towns and rural areas). Participants: A total of 8623 participants aged 48–92 years attended the Eye Study and underwent assessment of visual acuity, autorefraction, biometry, tonometry, corneal biomechanical measures, scanning laser polarimetry, confocal scanning laser ophthalmoscopy, fundal photography and automated perimetry. Outcome measures: Visual impairment was defined according to the WHO classification and the UK driving standard, and was based on presenting visual acuity. Summary measures of other ophthalmic measurements are also presented. Results: The prevalence (95% CI) of WHO-defined moderate-to-severe visual impairment and blindness was 0.74% (0.55% to 0.92%). The prevalence (95% CI) of presenting visual acuity worse than the UK driving standard was 5.87% (5.38% to 6.37%). Older age was significantly associated with visual impairment or blindness (p<0.001). Presenting visual acuity worse than UK driving standard was associated with older age (p<0.001), female sex (p=0.005) and lower educational level (p=0.022). Conclusions: The prevalence of blindness and visual impairment in this selected population was low. Visual impairment was more likely in older participants, women and those with a lower educational level.